Technical condition of pre-war buildings in the face of new transport investments on the example of a townhouse from 1912 - Marek Dohojda; Katarzyna Jeleniewicz; Joanna Witkowska-Dobrev; Olga Szlachetka (Acta Scientiarum Polonorum. Architectura)
The subject of the paper is an analysis a new building investments impact on the already existing buildings in a tight, compact city construction. The problem was discussed in two ways in the paper. Firstly, by identifying a group of factors that are caused by a new construction investments which could effect on neighbouring objects. Secondly, by correct technical condition assessment of existing buildings, methods for improving it or using technologies, that are also aimed to minimising the neighbouring investments impact. The issue was discussed based on a pre-war building located in the Praga Północ District in Warsaw.